Geographic Clustering and Productivity: An Instrumental Variable Approach for Classical Composers - Karol Jan Borowiecki (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
It is difficult to estimate the impact of geographic clustering on productivity because of endogeneity issues. I use birthplace-cluster distance as an instrumental variable for the incidence of clustering of prominent classical composers born between 1750 and 1899. I find that geographic clustering strongly impacts the productivity of the clustering individuals: composers were approx. 33 percentage points more productive while they remained in a geographic cluster. Top composers and composers who migrated to the cluster are the greatest beneficiaries of clustering. The benefit depends on the clustering intensity and has a long-term impact.
Keywords: J24; J61; N90; 330; geographic concentration; cities; mobility; productivity; urban history; composer